Panoptictrl + Facebook as means of control over its users - Bertulfo, Aimee Ruth Castro 1991- (2012)
"This study seeks to prove Facebook a means of control over its users with the assumption that it acts as a disciplinary or reinforcement institution to them. By examining Facebook's interface and interviewing selected users, I hope to expose the illusion of control given to the users through the various options Facebook offers. In this way, I seek to prove that the minds and bodies of the users are controlled, without their knowledge, in the guise of Facebook as a social networking site. In this light, I apply Jeremy Bentham's (1995) discourse of the Panopticon in order to prove how the minds of the users are being controlled by Facebook. On the other hand, I utilize Foucault's (1979) discussion of the docile bodies in illustrating how the physical bodies of the users are being coerced by the medium. With this, I employ textual analysis in analysing both Facebook's interface and the answers of the respondents I interviewed online. This study concludes that Facebook is used as a controlling mechanism to where its users are subjected. The all-seeing gaze is the regime of truth created by the different social institutions (e.g, school, church, family, etc.) of whose values are reinforced by and within the medium. Hence, the medium acts as disciplinary or reinforcement institution by controlling both the physical bodies and minds of its users in order to contain them within the truth created by society."